Strength Analysis of Micro Wind Turbine Blade Structure Made of Composite Material Using Finite Element Analysis - Maulana, Rafi Arifin; Puspitasari, Dewi; Abdi, Ferly Isnomo; Nugroho, Aji (Journal of Engineering Science and Technology Management (JES-TM), 2026)
This study analyzes the Structural Strength of micro wind turbine blades made of CFRP and GFRP composites using the Finite Element Analysis (FEA) method. Aerodynamic loads are obtained from QBlade simulations at a wind speed of 12 m/s and applied as non-uniform pressure on the blades. Composite modeling is performed with ANSYS Composite PrepPost (ACP) using a 4-ply laminated composite configuration with fiber orientations of 0°, 45°, −45°, and 90° and varying ply thicknesses along the blade. Static analysis shows that the CFRP blade produces a Von Mises stress of 15,648 MPa with a maximum displacement of 3.1616 mm, while the GFRP blade produces a stress of 12,786 MPa with a maximum displacement of 6,947 mm. These results indicate that CFRP has better Structural stiffness than GFRP, making it more suitable for micro wind turbine blade applications that require high Structural stability.